Landscape values in the daily life of coffee growers, references for the sustainable management of the territorial heritage in Quindío, Colombia (2021)
The role of rural inhabitants in shaping agrarian landscapes and heritages, in many definitions and approaches, is reduced to their historical influence. In the study, however, coffee growers are put first in their daily actions in relation to the cultural landscape.  The research objectives focused emic interest on the values and meanings that coffee growers assign to the farm. From the qualitative study with a phenomenological-interpretative approach that used in-depth interviews and participant observation as main instruments, values and meanings were identified and they give meaning to daily life and the conditions in which the processes of appropriation of the rural patrimony take place around the historical-spatial and socio-cultural rootedness. This externalization of meanings gives an understanding of the complexity of processes of valuation, resignification and vindication from which guidelines are proposed for the sustainable management of the heritage landscape.